Regional Policy Reactions to Demographic Change in Sparsely Populated, Peripheral Areas: Evidence from a Survey in Germany - Küpper, Patrick (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
Sparsely populated, peripheral areas are particularly affected by demographic changes. Regional policy offers a framework for reacting to the resulting challenges. The research question is: how does regional policy in sparsely populated, peripheral areas react to the challenges of demographic change? The contribution presents empirical survey data of the current practice. For this purpose, always one representative of regional development initiatives and counties (Landkreise) were asked to answer the questionnaire. The results indicate the application of counteraction strategies, the pursued spatial decentralisation, the dominance of public actors and the utilisation of strategic planning concepts. In the dimension of the mode of interaction, no clear tendency could be detected. Here, co-operation and unilateral action seem to coincide in practice.